Sejarah Gereja di Indonesia : Peran Misionaris Dalam Penyebaran Kekristenan - Surimawati Laia; Υuslina Halawa (LPPM - STT Kadesi Bogor, 2025)
The history of the spread of Christianity in Indonesia cannot be separated from the role of missionaries who came during the colonial period. This research aims to explore the role of missionaries in the spread of Christianity in Indonesia and its impact on social, educational and political changes in the country. Missionaries, both Catholic and Protestant, played a dual role in this process: on the one hand, they sought to spread Christianity; on the other hand, they also functioned as colonial agents that strengthened colonial power. In this context, the Christianization process is often seen as part of a colonial strategy to maintain dominance over local communities. The social impact of the spread of Christianity was significant, especially in shaping new social structures. Missionaries introduced a formal education system that gave access to communities that were previously unreached by education, such as in the Minahasa and Tapanuli regions. The education provided by missionaries covered basic learning, including reading, writing and arithmetic, which became an important foundation for the development of Indonesian society. However, the spread of Christianity also led to social tensions and conflicts, especially in areas where the majority of the population is Muslim. These tensions, according to some observers, were the result of the close relationship between Christianity and colonial rule. These conflicts still continue today.